UNDERSTANDING THE MINORITY MUSLIM COMMUNITY IN SINGAPORE: ISSUES AND CHALLENGES - Yusof, Norhafezah (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2018)
Based upon interviews with experts in Singapore, this research aims to investigate the struggle of the Muslim minorities in Singapore in terms of Islamic religious sources, practices, and educational values. Competitive religious resources, undervalued Islamic education, and freedom from fatwa legitimation have shaped the Muslim Singaporean framework in adjusting Muslims’ needs in search for authentic sources, practice Islamic values, and manage Islamic education in the community. Drawing from Turner’s conception on the space of liminality, this study attempts to understand the challenges faced by the Muslim minority in Singapore.